Preparation and characteristics of various rare earth nitrides - Imamura, H.; Imahashi, T.; Zaimi, M.; Sakata, Y. (2008)
Active nanocrystalline nitrides of EuN and YbN with high surface areas were successfully prepared by the thermal decomposition of the rare earth amides (Eu(NH2)2, Yb(NH2)2 and Yb(NH2)3). For the preparation of CeN, PrN and NdN, the direct reaction of the rare earth metals with ammonia was extensively studied to determine optimal conditions. In the reaction of rare earth metals with ammonia, hydrides besides the nitrides were competitively formed. The reaction conditions such as temperatures and ratios of ammonia to rare earth metal were crucial in preferential formation of nitride. The nanocrystalline YbN and EuN readily absorbed large amounts of ammonia even at room temperature upon contact with ammonia (13.3 kPa). The absorbed ammonia existed in at least two forms on/in the nitride; the one was surface-adsorbed ammonia and the other ammonia absorbed in the nitride in a decomposed state. The properties of ammonia absorbed by the nitride were further evaluated by temperature-programmed desorption (TPD), FT-IR and XRD techniques.